HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP PERAWAT DENGAN PELAKSANAAN MOBILISASI DINI PADA PASIEN POST OPERASI DI RUANG BEDAH DAN VIP RSU MAYJEN H.A THALIB KERINCI TAHUN 2017 - Novita Amri (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Based on data of the World Health Organization (WHO), the number of patients with surgery reached a very significant increase from year to year. Recorded in 2011 there were 140 million patients in all hospitals in the world, whereas in 2012 the data increased by 148 million. The mobilization is very important to accelerating the recovery and reducing the risk for long bedrest such as the stiffness or tension in the muscles of the body, blood circulation disorders, and impaired peristalsis or micturition. The purpose of this study to determine the relationship of the nurses knowledge level and attitude with the implementation of early mobilization in postoperative patients in the operating room and VIP Danau Lingkat RSUD Mayjen H.A Thalib Kerinci in 2017. This type of research is descriptive analytic research with cross sectional design, with a sample of 40 people. Data collected through interviews and questionnaires given to the respondent, then the data were analyzed by Univariate and Bivariate Analysis showed (55.0%) of respondents are not good on implementing of early mobilization, (60.0%) of respondents have low levels of knowledge, (57.5%) of respondents who have a negative attitude. There is a relationship between the level of knowledge with the implementation of early mobilization (p-value = 0.028), there is a relationship between atttitude with the implementation of early mobilization in the operating room and VIP Danau Lingkat RSUD Mayjen H.A Thalib Kerinci in 2017. Keywords : Mobilization, Knowledge, Attitude References : 30 (2000-2015)